Glacier-specific factors drive differing seasonal and interannual dynamics of Nunatakassaap Sermia and Illullip Sermia, Greenland. Issue 1 (31st December 2023) - Carr, J.R.; Carr, E.; Ross, N.
ABSTRACT: Accelerated ice discharge from marine-terminating outlet glaciers accounted for ~48 percent of ice loss from Greenland between 1992 and 2018, and the northwest has been the largest source of dynamic ice loss. Here, we assess the dynamics of two neighboring northwest Greenland glaciers, Nunatakassaap Sermia (NS) and Illullip Sermia (IS), for 2000 to 2020. Retreat rates at NS far exceeded those at IS, and NS accelerated and thinned substantially following the loss of its ice tongue. This was initially driven by loss of buttressing, followed by feedbacks between thinning, surface slope, and effective pressure, as NS retreated into a deeper and wider section of its fjord. At IS, acceleration and thinning were limited due to its location on a bedrock ridge. At NS, net retreat occurred when seasonal retreat persisted through the winter, whereas at IS it resulted from higher summer retreat rates. The timing of seasonal cycles in frontal positions and ice velocities differed markedly between NS and IS: we suggest that ice velocities respond to seasonal meltwater availability at IS and terminus position variations at NS. Overall, our results demonstrate that the dynamic behavior of NS and IS differs markedly at seasonal to decadal timescales and highlight the importance of glacier-specific factors.